(3cJGH aj GdJaSjQ GdTjYjs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdhGMO GdCMO GdefaQO GdPj dG ef TjA cGf hdG ef TjA Ndb eG chf Hd bOQI HCf ef GdCTjGA hHGfJ GdCTjGA efg adjSJ dg UaI JfGd (B() (3hdG MO jVQH ajg GdCeKGd s
(3BNQgG (B:s
(3ShQI CQCjJ hgj SHY BjGJ HSe Gddg GdQMef GdQMje aj CHj Lgd hcaGQ bQjT aPdc GdPj jOY GdjJje hdG jMV Ydi WYGe GdeScjf Ke bGd ahjd ddeUdjf GdPjf ge Yf UdGJge SGghfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJaSjQ hYdhe GdbQBfs